MENINGKATKAN KEMAMPUAN MENGENAL BENTUK-BENTUK GEOMETRI MELALUI MEDIA PUZZLE (BONGKAR PASANG) PADA ANAK USIA 4 – 5 TAHUN DI TK PERTIWI KABUPATEN GOWA - Abd. Hakim Naba (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2018)
Abstract: Improving the Ability to Know Geometry Forms Through Puzzle Media (Unloading)in Children 4 - 5 years old at the Pertiwi Kindergarten in Gowa Regency. The study aims todetermine the ability to recognize geometric forms through media puzzles (unloading pairs) in earlychildhood 4-5 years in TK Pertiwi, Gowa Regency. This research is a classroom action research with30 research subjects. Data collection techniques use puzzles (unloading). The study was conductedthrough two cycles, with each cycle consisting of four stages, namely planning, implementation,observation and reflection. The results of data analysis obtained in the first cycle the average percentageof completeness in learning the introduction of geometric forms have not reached the indicator that isequal to 54.81%, while the average percentage of completeness in learning the introduction of geometricshapes in students in the second cycle activities has developed which is very good at 78.89%. This studyshows a significant increase in the introduction of geometry. The results of this research show thatpuzzle games can improve the introduction of geometry in 4-5 year old children in TK Pertiwi, GowaRegency.